2021
DOI: 10.1111/ced.14601
|View full text |Cite
|
Sign up to set email alerts
|

Slack as a virtual undergraduate dermatology community: a pilot study

Abstract: Background. Dermatology is under-represented in UK undergraduate curricula, and with a diagnostic and educational toolkit that is heavily centred on face-to-face (F2F) clinical examination, dermatology education has been disproportionately affected by the COVID-19 pandemic. Online channel-based messaging apps such as Slack offer an opportunity to engage students in remote, multimodal collaborative learning by reproducing a classroom environment in the virtual space. Aim. To determine the feasibility, acceptabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 18 publications
(25 reference statements)
0
11
0
6
Order By: Relevance
“…The success of a programme delivered through a TBMA depends on clear understanding and application of the educational theory relevant to channel‐based TEL. The CoI framework focuses on the intentional development of an online community (e.g., Derm Hub 2 ) where the ultimate emphasis is to foster conversations that will lead to epistemic engagement. CoI was originally proposed in the early 2000s to facilitate understanding of learning through computer conferencing and has since been adapted to consider online learning in its entirety.…”
Section: Underpinning Tbma‐based Learning With Educational Theorymentioning
confidence: 99%
See 4 more Smart Citations
“…The success of a programme delivered through a TBMA depends on clear understanding and application of the educational theory relevant to channel‐based TEL. The CoI framework focuses on the intentional development of an online community (e.g., Derm Hub 2 ) where the ultimate emphasis is to foster conversations that will lead to epistemic engagement. CoI was originally proposed in the early 2000s to facilitate understanding of learning through computer conferencing and has since been adapted to consider online learning in its entirety.…”
Section: Underpinning Tbma‐based Learning With Educational Theorymentioning
confidence: 99%
“…We introduced a journal club focused on articles linked to the undergraduate dermatology curriculum, which offered insights into the critical appraisal process as well as promoting debate and discussion on recent research. Feedback by students showed that they were highly satisfied with this strategy 2 …”
Section: Programme Designmentioning
confidence: 99%
See 3 more Smart Citations